Comparison of Results After Facial Fat Grafting with Filtered and Washed Fat Versus Centrifuged Fat - Samuel, Tabish; Hameed, Shahid; Aslam, Rizwan; Ahmed, Rao Saood; Butt, Wajih Ud Din; Ayub, Afia (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To compare the centrifuged fat versus filtered and washed fat for facial fat grafting in terms of patient satisfaction and subjective/objective appearance.Study Design: Comparative prospective study.Setting/Duration of Study: Department of Plastic Surgery, CMH, Rawalpindi Pakistan, from Aug 2017 to Jan 2020.Methodology: A total of 64 patients (32 in each group) requiring facial fat grafting who fulfilled the sample selection criteria were included in the study. Patients who had received facial cosmetic surgery previously had systemic comorbid or were suffering from active infections were excluded. Group-A patients received centrifuged fat grafts, while Group-B patients received filtered and washed fat grafts. All patients were followed for patient satisfaction and subjective/objective appearance.Results: In Group-A, 23 (71.9%), 3 (9.4%), and 6 (18.7%) patients were happy, just satisfied and unhappy with the overall results of the procedure, respectively, while these numbers were 25 (78.1%), 3 (9.4%), and 4 (12.5%) in Group-B (p=0.785). Patients’ evaluation of their general appearance post-procedure (scored out of 10) showed a mean score of 6.53 ± 2.46 in Group-A and 6.72 ± 2.19 in Group-B (p=0.749). Scoring for a general appearance by an expert panel showed a mean score of 6.72 ± 2.16 in Group-A and a mean score of 7.13 ± 1.81 in Group-B (p=0.418).Conclusion: There is no difference between centrifugation and filtration/washing of fat grafts for facial grafting regarding patient satisfaction and subjective/objective appearance.